Chemical and microbiological stability study of a diazepam suspension - Rocha, J (2019)
Introduction: Drugs produced by pharmaceutical industry are limited to some dosages and forms that do not cover all therapy needs. Thus, the compounding drugs appear as a custom solution for several situations. One of those formulations is the diazepam suspension, produced in some hospitals with an empirical expiration date of 14 days.